101 Cost-effectiveness of vitamin d and exercise in preventing injurious falls among older women. (1st September 2016) - Patil, Radhika; Kolu, Päivi; Raitanen, Jani; Valvanne, Jaakko; Kannus, Pekka; Karinkanta, Saija; Sievänen, Harri; Uusi-Rasi, Kirsti
Abstract : Background: Costs of falling in older persons are high, both to individuals and to society. Both vitamin D and exercise are suggested to reduce the risk of falls. This study assessed the cost-effectiveness of vitamin D supplementation and exercise, separately and combined, in preventing medically attended injurious falls among older Finnish women. Methods: Economic evaluation was conducted alongside a previously published 2-year randomised controlled trial where 409 community-dwelling women aged 70 to 80 years were recruited into four groups: 1) no exercise + placebo (D−Ex−) 2) no exercise + vitamin D 800 IU/day (D+Ex−) 3) exercise + placebo (D−Ex+) 4) exercise + vitamin D 800 IU/day (D+Ex+). Outcomes were medically attended injurious falls and fall-related health care utilisation costs over the intervention period, the latter evaluated from a societal perspective based on 2011 unit costs. Incremental cost-effectiveness ratios (ICER) were calculated for the number of injurious falls per person-year prevented, and uncertainty estimated using bootstrapping. Results: Incidence rate ratios (95% CI) for medically attended injurious falls were lower in both Ex+ groups compared with D−Ex−: 0.46 (0.22 to 0.95) for D−Ex+, 0.38 (0.17 to 0.81) for D+Ex+. Step-wise calculation of ICERs resulted in exclusion of D+Ex− as more expensive and less effective. Recalculated ICERs were €221 for D−Ex−, €708 for D−Ex+ and €3, 820 for D+Ex+; bootstrapping indicated 93% probability that each injurious fall avoided by D−Ex+ per person-year costs €708. At a willingness to pay of €3, 000 per injurious fall prevented, there was an 85.6% chance of the exercise intervention being cost-effective in this population. Conclusions: Exercise was effective in reducing fall-related injuries among community dwelling older women at a moderate cost. Vitamin D supplementation had marginal additional benefit. The results provide a firm basis for initiating feasible and cost-effective exercise interventions in this population.